Augmentation of diethylnitrosamine–induced early stages of rat hepatocarcinogenesis by 1,2-dimethylhydrazine - Charatda Punvittayagul (2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group Diethylnitrosamine (DEN) and 1,2-dimethylhydrazine (DMH) are classical carcinogens used in experimental rodent carcinogenesis. However, the interaction effects of these carcinogens on biochemical and molecular changes during carcinogenesis have not been investigated. Therefore, the effect of DEN and DMH co-administration on preneoplastic lesion formation and its molecular mechanism in rats were determined. Triple intraperitoneal administrations of DEN were made before, during or after double subcutaneous injections of DMH. At week 8 of the experiment, the preneoplastic hepatic glutathione-S-transferase placental form (GST-P) positive foci and colonic aberrant crypt foci (ACF) were analyzed. The combined treatment of these carcinogens increased toxicity to rats. Administration of DMH alone did not induce hepatic GST-P positive foci, while co-treatment with DMH enhanced hepatic GST-P positive foci formation. However, DEN did not influence the size or number of colonic ACF. The treatment with DMH alone induced CYP2E1 and P450 reductase, demonstrating that DMH enhanced DEN metabolism in DEN- and DMH-treated rats. These findings were related to increases in hepatic O6-methylguanine DNA adducts and hepatotoxicity, which are associated with the induction of cell proliferation and liver cancer development. DEN-induced early stages of rat hepatocarcinogenesis were synergistically promoted by DMH via metabolic enzyme induction leading to enhanced DNA mutation and hepatocarcinogenicity.